2017
DOI: 10.3727/096368916x693563
|View full text |Cite
|
Sign up to set email alerts
|

A Novel CXCR4 Antagonist CX549 Induces Neuroprotection in Stroke Brain

Abstract: C-X-C chemokine receptor type 4 (CXCR4) is a receptor for a pleiotropic chemokine CXCL12. Previous studies have shown that the acute administration of the CXCR4 antagonist AMD3100 reduced neuroinflammation in stroke brain and mobilized bone marrow hematopoietic stem cells (HSCs). The purpose of this study was to characterize the neuroprotective and neurotrophic effect of a novel CXCR4 antagonist CX549. We demonstrated that CX549 had a higher affinity for CXCR4 and was more potent than AMD3100 to inhibit CXCL12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 31 publications
(56 reference statements)
1
32
0
Order By: Relevance
“…In comparison with AMD3100, compound 131 exerts better mobilization of HSCs for transplantation and induces behavioral improvement. These in vivo data support that it is a potent anti‐inflammatory agent with great neuroprotective potential against ischemic brain injury, and exhibit clinical implications for the treatment of stroke …”
Section: Therapeutic Potential For Intervention With Cxcl12/cxcr4 Axissupporting
confidence: 52%
See 4 more Smart Citations
“…In comparison with AMD3100, compound 131 exerts better mobilization of HSCs for transplantation and induces behavioral improvement. These in vivo data support that it is a potent anti‐inflammatory agent with great neuroprotective potential against ischemic brain injury, and exhibit clinical implications for the treatment of stroke …”
Section: Therapeutic Potential For Intervention With Cxcl12/cxcr4 Axissupporting
confidence: 52%
“…Chronic nonhealing foot ulcers are the common causes of nontraumatic amputation and hospitalization among diabetics in the developed world. Different studies have shown that delayed wound closure is associated with diminished circulating PGCs in diabetic mice . Plerixafor TM improved diabetes associated pathology by reducing bone marrow CXCL12 levels, enhancing PGCs mobilization, and accelerating the wound healing process .…”
Section: Therapeutic Potential For Intervention With Cxcl12/cxcr4 Axismentioning
confidence: 97%
See 3 more Smart Citations